Diet Rich in Lard Promotes a Metabolic Environment Favorable to Trypanosoma cruzi Growth - Souza, Débora Maria Soares de; Silva, Maria Cláudia; Farias, Silvia Elvira Barros; Menezes, Ana Paula de J.; Milanezi, Cristiane Maria; Lúcio, Karine de P.; Paiva, Nívia Carolina N.; Abreu, Paula Melo de; Costa, Daniela Caldeira; Pinto, Kelerson Mauro de Castro; Costa, Guilherme de Paula; Silva, João Santana; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background:Trypanosoma cruzi is a protozoan parasite that causes Chagas disease and affects 6–7 million people mainly in Latin America and worldwide. Here, we investigated the effects of hyperlipidic diets, mainly composed of olive oil or lard on experimental T. cruzi infection. C57BL/6 mice were fed two different dietary types in which the main sources of fatty acids were either monounsaturated (olive oil diet) or saturated (lard diet). Methods: After 60 days on the diet, mice were infected with 50 trypomastigote forms of T. cruzi Colombian strain. We evaluated the systemic and tissue parasitism, tissue inflammation, and the redox status of mice after 30 days of infection. Results: Lipid levels in the liver of mice fed with the lard diet increased compared with that of the mice fed with olive oil or normolipidic diets. The lard diet group presented with an increased parasitic load in the heart and adipose tissues following infection as well as an increased expression of Tlr2 and Tlr9 in the heart. However, no changes were seen in the survival rates across the dietary groups. Infected mice receiving all diets presented comparable levels of recruited inflammatory cells at 30 days post-infection but, at this time, we observed lard diet inducing an overproduction of CCL2 in the cardiac tissue and its inhibition in the adipose tissue. T. cruzi infection altered liver antioxidant levels in mice, with the lard diet group demonstrating decreased catalase (CAT) activity compared with that of other dietary groups. Conclusions: Our data demonstrated that T. cruzi growth is more favorable on tissue of mice subjected to the lard diet. Our findings supported our hypothesis of a relationship between the source of dietary lipids and parasite-induced immunopathology.